2013
DOI: 10.1152/ajpregu.00542.2012
|View full text |Cite
|
Sign up to set email alerts
|

Reduced c-Fos expression in medullary catecholaminergic neurons in rats 20 h after exposure to chronic intermittent hypoxia

Abstract: Persons affected by obstructive sleep apnea (OSA) have increased arterial blood pressure and elevated activity in upper airway muscles. Many cardiorespiratory features of OSA have been reproduced in rodents subjected to chronic-intermittent hypoxia (CIH). We previously reported that, following exposure to CIH, rats have increased noradrenergic terminal density in brain stem sensory and motor nuclei and upregulated expression of the excitatory α(1)-adrenergic receptors in the hypoglossal motor nucleus. This sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…The upregulation of C/EBP β and c-Fos activity and function in hypoxic states is potentially problematic for the retina. However, Herr KB et al 35. reported that chronic intermittent hypoxia reduced the baseline activity of c-Fos in medullary catecholaminergic neurons.…”
Section: Discussionmentioning
confidence: 98%
“…The upregulation of C/EBP β and c-Fos activity and function in hypoxic states is potentially problematic for the retina. However, Herr KB et al 35. reported that chronic intermittent hypoxia reduced the baseline activity of c-Fos in medullary catecholaminergic neurons.…”
Section: Discussionmentioning
confidence: 98%
“…Adrenergic neurons in the subcoeruleus and neighboring areas play roles in upper airway muscle responses to intermittent hypoxia (Herr et al, 2013). …”
Section: “Classic” Respiratory and Cardiovascular Area Injurymentioning
confidence: 99%
“…Slides from all three conditions were stained at the same time, and quantification of cFos labeling was performed blindly with respect to the origin of the slides. cFos is induced by the activation of multiple signal transduction pathways (Hoffman and Lyo, 2002;Hassani et al, 2009), and changes in its expression have been related to differences in neuronal activity in particular cell populations (Hoffman and Lyo, 2002;Benincasa Herr et al, 2013). Although cFos induction is not a straightforward marker of increased neuronal firing rates, it does indicate the onset of activityrelated changes in neuronal metabolism or morphology that require changes in gene expression (Cirelli and Tononi, 2000;Benincasa Herr et al, 2013).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…cFos is better considered as a marker of metabolic/structural changes that require changes in gene expression (Cirelli and Tononi, 2000), induced in response to combinations of input events. Even though cFos is not a direct read-out of generalized cell electrical activity, it has been (and is still being) used to successfully map specific neural circuitry involved in brain responses to hypoxia in both adult (Berquin et al, 2000;King et al, 2012;Benincasa Herr et al, 2013) and fetal mammals (Breen et al, 1997;Nitsos and Walker, 1999b). cFos thus provides one of the few ways to simultaneously survey the responses of large populations of neurons with single-cell resolution in embryos (Hoffman and Lyo, 2002).…”
mentioning
confidence: 99%